2019
DOI: 10.1039/c8nj05017a
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazoline-based colorimetric and fluorescent probe for detection of sulphite

Abstract: This work reports a novel Michael addition based sensor for fluorescence detection of sulphite in river water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This result indicates that a large charge separation occurred in the neutral form of 4 , whereas no charge separation occurred in the protonated form of 4 . This further suggests that protonated and unprotonated 4 prefer the locally excited (LE) character in the excited state and ICT process, respectively. , Therefore, the LE characteristics of the protonated species of 4 formed in MeOH were strong even in polar solvents such as MeOH without emission quenching through the TICT state.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This result indicates that a large charge separation occurred in the neutral form of 4 , whereas no charge separation occurred in the protonated form of 4 . This further suggests that protonated and unprotonated 4 prefer the locally excited (LE) character in the excited state and ICT process, respectively. , Therefore, the LE characteristics of the protonated species of 4 formed in MeOH were strong even in polar solvents such as MeOH without emission quenching through the TICT state.…”
Section: Resultsmentioning
confidence: 96%
“…This further suggests that protonated and unprotonated 4 prefer the locally excited (LE) character in the excited state and ICT process, respectively. 37,38 Therefore, the LE characteristics of the protonated species of 4 formed in MeOH were strong even in polar solvents such as MeOH without emission quenching through the TICT state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pyrazoline derivatives as a kind of important five-member nitrogen-containing compound are ubiquitous in natural products. , With the CNNHC functional group, pyrazoline derivatives possess a broad spectrum of biological activities and have attracted considerable interests in functional materials such as medicine, fluorescent substances, and energetic fuel precursors. , …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the practical application of the probes was illustrated by utilizing a paper test strip method for HSO 3 − detection. It was observed that the paper discolored from orange or yellow to blue [ 104 ], confirming its potentiality to detect HSO 3 − in water samples. In this study, a simple replacement of end groups by thiophene surpassed the response time by 1.2 times and the detection limit by 1.5 times.…”
Section: Fluoridementioning
confidence: 96%